Understanding ecosystem services for climate change resilience in coastal environments: a case study of low-canopy sub-tidal seagrass beds in Fiji - Muna, Lency Royce; Brodie, Gilianne; Singh, Awnesh; Hills, Jeremy; Wandres, Moritz; Damlamian, Herve (Frontiers in Marine Science, 2023)
The Pacific Island Countries (PICs) are exposed to extreme wave conditions which are projected to be exacerbated by rising sea levels due to climate change, prompting the need for strategic planning of coastal communities and assets. Nature-based protection has been proposed as a sustainable solution to promote the resilience of coastal areas from physical impacts such as wave-induced erosion. In this study, we investigate the potential coastal protection service of shallow subtidal low-canopy seagrass beds, dominated by Halodule uninervis, on the rate of wave height and wave energy reduction on a barrier and fringing reefs. The data was collected using bottom-mounted pressure sensors to measure wave height and energy reduction as waves moved toward the shoreline across the seagrass beds. The results show that on average, the seagrass beds were able to reduce wave height by 30% and energy by 47% in both reef environments. These reduction rates are strongly influenced by water depth, seagrass characteristics, and local reef conditions. Based on these results, seagrasses can strengthen the resilience of coastal shorelines to wave erosion, thus conserving healthy low-canopy seagrass habitats has measurable benefits for shoreline protection in Fiji and other PICs.